SIRT1 in the Development and Treatment of Hepatocellular Carcinoma - Farcas, Marius; Gavrea, Andrei-Alexandru; Gulei, Diana; Ionescu, Calin; Irimie, Alexandru; Catana, Cristina S.; Berindan-Neagoe, Ioana (Frontiers in Nutrition, 2019)
Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related death worldwide. Current treatment option for inoperable HCCs have decreased therapeutic efficacy and are associated with systemic toxicity and chemoresistance. Sirtuin 1 (SIRT1) is a nicotinamide adenine dinucleotide–dependent enzyme which is frequently overexpressed in HCC, where it promotes tumorigenicity, metastasis, and chemoresistance. SIRT1 also maintains the tumorigenic and self-renewal proprieties of liver cancer stem cells. Multiple tumor-suppressive microRNAs (miRNAs) are downregulated in HCC and, as a consequence, permit SIRT1-induced tumorigenicity. However, either directly targeting SIRT1, combining conventional chemotherapy with SIRT1 inhibitors or up-regulating tumor-suppressive miRNAs may improve therapeutic efficacy and patient outcomes. Here, we present the interaction between SIRT1, miRNAs, and liver cancer stem cells and discuss the consequences of their interplay for the development and treatment of HCC.